Prevalence and determinants of unmet need for contraception in North Gonja District, Ghana - Anthony Wemakor; Humphrey Garti; Nawaf Saeed; Obed Asumadu; Bede Anyoka (BMC, 2020)
Abstract Background Unmet need for contraception contributes to the burden of unwanted pregnancies, which are correlated with a host of adverse maternal and child outcomes. The aim of this study was to determine the prevalence and identify the determinants of unmet need for contraception in North Gonja District, Ghana. Methods A cross-sectional survey involving 386 randomly selected women of childbearing age was conducted in North Gonja district, Ghana, with the use of a questionnaire in household interviews. Women were classified as having unmet need for contraception if they were fecund, sexually active and wished to postpone the next birth or halt childbearing completely but were not using any form of contraception. Chi-square/Fisher's exact test and logistic regression analysis were used to identify the determinants of unmet need. Results The mean age of the study population was 26.1 (±8.4) years and awareness on contraception was almost universal in the district (95.9%). The overall prevalence of unmet need for contraception was 38.9%, with 27.5% having unmet need for limiting and 12.2% unmet need for spacing. In multivariate analysis, compared to women aged 25-29 years, those aged 20-24 years [Adjusted Odds Ratio (AOR) 0.26; 95% Confidence Interval (CI) 0.11-0.58] and 30 years and above (AOR 0.25; 95% CI 0.09-0.73) were less likely to have unmet need for contraception. However, uneducated women (AOR 5.06; 95% CI 1.07-24.01) compared with those educated to tertiary level; those unaware of family planning (AOR 3.93; 95% CI 1.12-13.80) compared to those aware; and those who had not previously practised contraception (AOR 1.81; 95% CI 1.09-3.00) compared to those who did were more likely to have unmet need. Conclusions The present study found high prevalence of both awareness on and unmet need for contraception among the study population. Unmet need for contraception is associated with age, educational status, awareness on family planning and previous contraception practice. Educational campaigns to promote contraception should prioritize women of middle age and low educational status. Further studies are needed to understand the low correlation between awareness on and unmet need for contraception.